Past in the present: Mount Ślęża according to pierre nora’s “sites of memory” (lieux de mémoire) concept - Pawleta, Michał (Folia Praehistorica Posnaniensia, 2018)
In article I propose taking a look at the Mount Ślęża in Poland in the context of Pierre Nora’s lieux de mémoire concept. Ślęża is an important heritage site as although it has been the topic of many studies and scientific investigations, interest in this unusual mountain goes well beyond scientific discourse. This paper focuses on not only what Ślęża meant to prehistoric people but mainly on its contemporary significance, with specific attention to the various functions that it fulfils today. By revealing the breadth of discourses on Ślęża and highlighting its vitality and relevance in the lives of many people, it also attmpts to put forward a dialogue between archaeologists, heritage professionals and groups holding alternative views on the current meaning or role of the Mount Ślęża.